STRATEGI PEMBELAJARAN BAHASA INGGRIS BERBASIS PESANTREN DI MA ROUDLOTUL MUBTADIIN BALEKAMBANG NALUMSARI JEPARA - Maftuhatun Nurul Millah (Intelegensia : Jurnal Pendidikan Islam, 2019)
Abstract      This research focused on English learning strategies based on pesantren at MA Roudlotul Mubtadiin Balekambang Nalumsari Jepara. The purpose of this study was to find out how the English learning strategy based on pesantren at MA Roudlotul Mubtadiin Balekambang Nalumsari Jepara. This research was a qualitative descriptive study. This type of research was a case study. The population of this study was all students at MA Roudlotul Mubtadiin Balekambang. Then the sample is 10th and 11th grade students at MA Roudlotul Mubtadiin Balekambang. In taking samples researchers used a purposive sampling technique. The data in this study were taken from two sources, namely primary data and secondary data. Data collection instruments in this study were observation, interviews, and documentation. The stages of data analysis in this research are data reduction, data presentation, and conclusion and verification. From the analysis of the data obtained that: 1) Planning started from the determination of academic calendar, making annual programs and semester programs, making syllabus and lesson plan (RPP). 2) The teacher implemented the plans that have been designed previously in the teaching and learning process. In the teaching and learning process there are three stages, namely pre activities, main activities, and post activities. 3) Learning reflection was carried out to find out the strengths and weaknesses during the learning process. So the teacher could find solutions to the shortcomings of the previous learning process.Keywords: English; Learning based on Pesantren; Learning Strategies